Assessment Of Thyroid Stimulating Hormone, Triiodothyronine, Luteinizing Hormone And Follicle-Stimulating Hormone Levels in Polycystic Ovary Syndrome - Deli, Doaa AbdAlzahra; Almammory, Ginan Kareem; Obaid, Khmaeel Mohsin (Medical Science Journal for Advance Research, 2024)
Bachgraund: Polycystic ovarian syndrome (PCOS) is the most prevalent endocrinopathy and reproductive condition with hyperandrogenism that affects young women of reproductive age., It is a disorder with many distinct faces that affects millions of women worldwide, and it causes them considerable emotional and physical suffering. The present study is designed to estimate the TSH, T3, LH, and FSH levels in women with polycystic ovarian syndrome (PCOS). The blood samples were collected from 60 females, 30 control, and 30 patients. A device named VIDAS was used to measure TSH, T3 LH, and FSH. The present results indicated that levels of TSH, LH, and FSH were elevated (P<0.05) significantly in the patient's group, while serum levels of Triiodothyronine decreased in the PCOS females group. According to the results of the current study, PCOS patients had hypothyroidism, which was demonstrated by elevated TSH, LH, and FSH levels.